2019
DOI: 10.1080/03019233.2018.1561385
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of blast furnace hearth condition: part I – a steady state simulation of hearth condition during normal operation

Abstract: A coupled flow and refractory model (CFRM) has been upgraded to assist engineers in understanding and interpreting the measured refractory temperature distributions in the hearth of a blast furnace hearth. CFRM describes the liquid flow distribution and heat transfer in the hearth, allowing various scenarios to be simulated involving coke bed properties, extent of hearth refractory wear, etc. The model was validated through comparison between measured refractory data and corresponding model predictions for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 16 publications
(32 reference statements)
0
8
0
Order By: Relevance
“…Refractory [1] 1560∼2780 1260 1∼21 Liquid iron 7737-0.5 T [23] Min(850, 0.50T + 298.98) [19,24] 59.85 [24] if T<T solidus 1214-0.826 T if T solidus ≤T ≤ T liquidus 0.0158 T [25] if T > T liquidus…”
Section: Typical Simulation Results and Validationmentioning
confidence: 99%
See 1 more Smart Citation
“…Refractory [1] 1560∼2780 1260 1∼21 Liquid iron 7737-0.5 T [23] Min(850, 0.50T + 298.98) [19,24] 59.85 [24] if T<T solidus 1214-0.826 T if T solidus ≤T ≤ T liquidus 0.0158 T [25] if T > T liquidus…”
Section: Typical Simulation Results and Validationmentioning
confidence: 99%
“…Material properties used in the simulation are listed in Table 1, including the thermal conductivity, heat capacity and density for the various hearth refractories as well as liquid iron. The property for each part of refractory is the same as that given elsewhere ( Table 2 in Part I [1]). Thus, only the range of refractory properties is given in Table 1.…”
Section: Computational Domain and Materials Propertiesmentioning
confidence: 99%
“…In particular, a lower coke rate leads to higher burden density and gravity forces, which Skull [9,10,28] 0 0 2.0 facilitate a sitting deadman in the hearth where the flow velocities and temperature at the bottom are low. [7,[19][20][21] A higher coal rate gives rise to a state in the lower furnace where coal fines are consumed slowly, deteriorating the deadman permeability. [16] For substantiating these arguments, the evolutions of bottom temperature (from TC1) and the coke and coal rates during Period 3 are shown in Figure 5, where it can be observed that the bottom temperature correlates well with the coke and coal rates.…”
Section: The Hearth Wear Modelmentioning
confidence: 99%
“…In practice, to help explain refractory temperature measurements and locate the 1150°C isotherm, numerical modelling has been applied and can be classified into two categories: (1) refractory conduction modelling, for one-, two-or three-dimensional (1D, 2D or 3D) conditions within the hearth refractory [3][4][5][6][7][8]; (2) modelling based on coupled fluid flow, heat and mass transfer in a domain including hearth refractory and the molten liquid bath [4,[9][10][11][12][13][14][15][16][17][18][19][20]. The former is mainly based on the inverse heat conduction technique considering heat transfer in the refractory and skull (solidification layer) while the latter provides more information about molten iron (and slag) flow and the heat transfer within the hearth.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, the Shear Stress Transport (SST) turbulence model has been applied to further enhance the simulation of critically important, near-wall flow in the hearth [22]. Based on SST, a Coupled Flow and Refractory Model (or CFRM) was developed and applied for industrial application [19,20].…”
Section: Introductionmentioning
confidence: 99%